Strategi Kepemimpinan Kepala Sekolah dalam Pengelolaan Operasional Pendidikan Islam - Cindy; Anggra Prima (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
This study aims to analyze the principal’s leadership strategy in managing Islamic education operations at Muhammadiyah Elementary School, South Sangatta, focusing on planning, organizing, actuating, and controlling (POAC), the implementation of Islamic leadership values, and the resulting impacts. This research employed a qualitative descriptive approach. The participants included the principal, vice principal for curriculum, teachers, and educational staff. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model consisting of data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that the principal implements leadership strategies through the POAC management functions integrated with Islamic values of trustworthiness (amanah), humility (tawadhu), righteous deeds (amal shalih), and piety (taqwa). These strategies positively influence the effectiveness of Islamic education management, reflected in strengthened religious culture, improved worship discipline, successful implementation of Tahfiz, Hizbul Wathan, and Tapak Suci programs, as well as enhanced collaboration among the school community.